Exploring folded space in urban Cape Town : unfolding the Strand / Adderley Street juncion - Willemse, Mariet (School of Architecture, Planning and Geomatics, 2017)
This thesis started with a personal interest as to what informs architectural form, specifically the folded, smooth or continuous form so visible in contemporary architecture. I was interested in the relationship between the formal 'folds' of contemporary architecture and the spatial theory of 'folded space'. In order to understand where these forms are coming from and whether or not the idea of 'folded space' could bring value to the construct of architecture in the South African context I had to gather a comprehensive understanding of the state of architecture in the 21" century and of course that meant researching the failures and successes of what went before. I have learned that the obsession with folded form comes from contemporary architecture's preoccupation with connection and complexity in architecture. In short; Modernism sought to group, zone and separate different spatial programs which were often translated into pure geometric forms, Post-Modernism reacted against the monotony of Modernism by juxtaposing exaggerated oppositions in form and spaces. Today, in the transitional phase from the late 20th century to the beginnings of the 21" century, contemporary architecture still struggles with the theme of connection and complexity in architecture. The idea of 'folded space' where previously unrelated elements are smoothly integrated within a continuous, but heterogeneous mixture seems to provide contemporary architects with an alternative to the purity of Modernism and the vulgar oppositions of Post-modernism. So the question contemporary architecture is faced with today is: How can architecture formulate a continuous mixture which still allows for variety complexity? The theory investigation concluded that the relevance of the folded space in the South African context could be the realization that through the folding or blurring of the relationship between previously unrelated programs, spaces and the building and its urban context, new and interesting social interactions might arise. The corner of Strand and Adderley Street on the station site proved an appropriate site on which to test this theory of 'folded space' on both a social and a spatial level. Although the site is situated on the most important intersection in the city it is known for its clear separations and barriers. The three levels in the center of the city, the underground, the ground and the above ground I station roof are separated both spatially and socially. The design project strives to experiment with ways in which to 'fold' the distinct spaces that are imminent, but repressed on this corner site in the heart of Cape Town's city. Through folding or connecting these spaces and programs that were previously separated the architecture will aim to act as a platform for social encounters amongst its users.